2019
DOI: 10.1371/journal.pone.0226249
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted resting-state brain functional network in methamphetamine abusers: A brain source space study by EEG

Abstract: This study aimed to examine the effects of chronic methamphetamine use on the topological organization of whole-brain functional connectivity network (FCN) by reconstruction of neural-activity time series at resting-state. The EEG of 36 individuals with methamphetamine use disorder (IWMUD) and 24 normal controls (NCs) were recorded, pre-processed and source-reconstructed using standardized low-resolution tomography (sLORETA). The brain FCNs of participants were constructed and between-group differences in netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…When these regions are impaired, the executive control systems may be affected as demonstrated by Volkow et al ( 2015 ) by specific impairments within the executive brain networks in MA addicts during the exposure to drug-associated cues. Khajehpour et al ( 2019 ) also reported that MA abusers differed in the gamma band in the paracentral lobule. It may be speculated that the substance-dependent individuals are unable to control their addiction-related behaviors (Khajehpour et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When these regions are impaired, the executive control systems may be affected as demonstrated by Volkow et al ( 2015 ) by specific impairments within the executive brain networks in MA addicts during the exposure to drug-associated cues. Khajehpour et al ( 2019 ) also reported that MA abusers differed in the gamma band in the paracentral lobule. It may be speculated that the substance-dependent individuals are unable to control their addiction-related behaviors (Khajehpour et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…Khajehpour et al ( 2019 ) also reported that MA abusers differed in the gamma band in the paracentral lobule. It may be speculated that the substance-dependent individuals are unable to control their addiction-related behaviors (Khajehpour et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…MDMA acts via serotonergic receptors and may cause disturbances of serotonergic pathways (Benningfield and Cowan, 2013) and electrophysiological changes that reflect recruitment of additional resources to perform cognitive tasks (Roberts et al, 2018). The other psychoactive substances used among PU, such as cocaine, amphetamine, and others may interact in a complex way and cumulative effect may impact the further increased brain activity (Zilverstand et al, 2018;Khajehpour et al, 2019). Still, little is known about the interactive impact of various illicit drugs on the human brain (Gouzoulis-Mayfrank and Daumann, 2006;Van Dam et al, 2008;Shevlin et al, 2017), regardless of the observed high frequency of polydrug use pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, hair sample analysis was not available for eight participants from the control group. However, it is important to note that biological measures of drug use (illicit substances or psychotropic medication) is rarely used in nonusing controls in the research field on cannabis (or other illicit drugs) and self-reported measures dominate for CU (Smith et al, 2017;Khajehpour et al, 2019;Rangel-Pacheco et al, 2020) or the urine/hair sample analyses detect cannabis use only (no other illicit drugs nor psychotropic medication) (Yücel et al, 2016;Prashad et al, 2018). That is why we would consider it as an additional value of our study and exclusion of this participants form analyses would make CG too small to obtain reliable results.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Newton et al (2003) showed 78 that the delta/δ and theta/θ bands, but not others, were elevated almost globally in the cortical subregions (Newton et al, 2003). The findings were partly supported by Khajehpour et al (2019), showing that delta/δ and gamma/γ powers were slightly, yet significantly, increased in a topographic analysis (Khajehpour et al, 2019). Alcohol is 82 believed to be inhibitory, mimicking GABA's effect on postsynaptic GABAA receptors (Olsen & Liang, 2017).…”
mentioning
confidence: 86%